2010
DOI: 10.1053/j.gastro.2010.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in TTC37 Cause Trichohepatoenteric Syndrome (Phenotypic Diarrhea of Infancy)

Abstract: Background Trichohepatoenteric syndrome (THES) is an autosomal recessive disorder characterised by life-threatening diarrhoea in infancy, immunodeficiency, liver disease, trichorrhexis nodosa, facial dysmorphism, hypopigmentation and cardiac defects. We attempted to characterise the phenotype and elucidate the molecular basis of THES. Methods Twelve patients with classical THES from 11 families had detailed phenotyping. Autozygosity mapping was undertaken in 8 patients from consanguineous families using 250k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
146
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(151 citation statements)
references
References 32 publications
2
146
1
2
Order By: Relevance
“…El efecto de dicha mutación se piensa que es multisistémico aunque se han encontrado, con estudios de inmunofluorescencia confocal, inadecuada distribución o expresión disminuida de múltiples proteínas transportadoras apicales en enterocitos yeyunales. 4 Fabre y su grupo observaron que 6 de 15 individuos que mostraban características clínicas de diarrea fenotípica de la infancia o síndrome tricohepatoentérico no mostraron la mutación en TTC37; consideraron a TTC37 homólogo al gen SKI3 de levaduras y este es un componente clave de un complejo multiproteínico denominado Ski, requerido para la vigilancia exosomal de descomposición del ARN y la vigilancia de la expresión de la fidelidad genética del propio ARN. Buscaron mutaciones en el gen ortólogo humano de SKI3 que resultó en la identificación de mutaciones deletéreas en el gen SKIV2L en los seis individuos referidos.…”
Section: Discussionunclassified
“…El efecto de dicha mutación se piensa que es multisistémico aunque se han encontrado, con estudios de inmunofluorescencia confocal, inadecuada distribución o expresión disminuida de múltiples proteínas transportadoras apicales en enterocitos yeyunales. 4 Fabre y su grupo observaron que 6 de 15 individuos que mostraban características clínicas de diarrea fenotípica de la infancia o síndrome tricohepatoentérico no mostraron la mutación en TTC37; consideraron a TTC37 homólogo al gen SKI3 de levaduras y este es un componente clave de un complejo multiproteínico denominado Ski, requerido para la vigilancia exosomal de descomposición del ARN y la vigilancia de la expresión de la fidelidad genética del propio ARN. Buscaron mutaciones en el gen ortólogo humano de SKI3 que resultó en la identificación de mutaciones deletéreas en el gen SKIV2L en los seis individuos referidos.…”
Section: Discussionunclassified
“…The estimated prevalence is 1/1,000,000 births. 1 44 cases have been published between 1982 and 2012. Literature reviewed showed that 9 clinical signs are associated with THE-S. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] Three are constant: intractable diarrhea, facial dysmorphism and hair abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…In case with abnormal antibody production, immunoglobulin administration may be required. 1 Patients with THE-S are also at increase risk of developmental delay, therefore early neurorehabilitative therapy should be started once developmental delay is identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations